Spiritual Crisis as a Unique Causal Predictor of Emotional and Characterological Impairment in Atheists and Agnostics: Numinous Motivations as Universal Psychological Qualities - Ralph L. Piedmont; Jesse Fox; Marion E. Toscano (Religions, 2020)
While there is a tremendous literature documenting the positive value of religious and spiritual (R/S) constructs on an array of psychosocial outcomes (e.g., health, resilience, coping ability), Spiritual Crisis (SC) reflects the negative side of the numinous in a way that stresses the value and importance of R/S constructs for psychological functioning. This study examined whether numinous constructs are more relevant to theists or represent universal psychological qualities. Using an MTurk-based sample comprising both theists and atheists (N = 1399; 800 women and 595 men, four gave no response), the predictive ability of SC on both affective and characterological distress was examined using both regression and SEM analyses. The results indicated that both theists and atheists understood the numinous in similar ways and that scores on SC were of equal incremental predictiveness for both groups. SEM analyses supported the causal model that understood SC to be a unique and independent (from the personality domains of the Five-Factor Model) predictor of these clinical outcomes. These findings stress the value of the numinous for understanding all clients and that psychological assessment needs to systematically address numinous constructs in order to ensure comprehensive treatment of psychological impairment.